Electron Microscopy of Friend Murine Leukemia Virus in the Mid-Gut of Experimentally Infected Mosquitoes - Hirumi, Hiroyuki (1971)
After 30 and 78 hr, Friend murine leukemia virus (FLV) particles were detected by electron microscopy in the mid-gut lumen of the mosquitoes Aedes aegypti (Linnaeus) and Anopheles stephensi Liston which had fed on leukemia BALB/c mice infected with FLV. Various developmental stages of the virions were observed within and on the surface of ingested blood cells, particularly young erythroblasts, as well as free in the lumen after budding. These preliminary findings indicate that FLV continues to multiply in the mid-gut of these species for at least 3 days despite the action of digestive enzymes. Detailed studies are in progress to determine the fate of FLV in these mosquito species.